Solvent-Free Efficient Synthesis of New 4-Thiazolidinones with a Fructose Scaffold through a Microwave-Assisted Cascade Multicomponent Reaction - Lorenzo, Fernando; Ocampo, Romina; Rodríguez, Diego F.; Santana-Romo, Fabián; Galdamez, Antonio; Zacconi, Flavia C.; Burrow, Robert A.; Mandolesi, Sandra; D’Accorso, Norma (Synthesis, 2024)
Using a chemoselective, sustainable and highly efficient method, new 4-thiazolidinones and 1,4-thiazepan-3-ones substituted with a glycosidic residue derived from d-fructose were synthesized. Microwave-assisted cascade multicomponent reaction under solvent-free conditions gave very good yields in short reaction times, which was followed by a nontoxic purification method of one of the diastereomers by precipitation–centrifugation. The new purified compounds isolated as diastereomers were evaluated as factor Xa (FXa) inhibitors.
Keywords: 4-thiazolidinones; 1,4-thiazepan-3-ones; carbohydrates; chemoselectivity; multicomponent reaction